Correlação entre as medidas lineares em radiografias panorâmicas e tomografias computadorizadas cone beam associadas ao seio maxilar - Rodrigues, Gustavo Henrique Campos; Rodrigues, Vinícius Anéas [UNESP]; de Barros, Stella Mendes; Ximenez, Michel Eli Lipiec; de Souza, Daniela Martins (My University, 2013)
Objective: To correlate linear measurements between digital panoramic radiographs (DPan) and cone beam computed tomography images (CBCT) of the maxillary sinus area. Method: Seventy-one paired site exams were selected, 37 from the right side and 34 from the left side, on digital panoramic radiographs and their corresponding CBCT images. The panoramic radiographs were obtained by the Orthopantomograph® evice and analyzed by the Image Tool v.3.0 software. The CBCT images were obtained by the i-CAT tomograph and analyzed by the Dental Slice software. Linear measurements of the distance between the lower cortical of the maxillary sinus to the sharpest molar cusp. Results: Comparison of the measurements revealed a moderate agreement and the values were significantly higher in the measurements on the compensated digital panoramic radiographs (p<0.05) with 1.75 to 2.15 mm (8 to 9%) magnification, compared with the CBCT images. Conclusion: It may be concluded that when panoramic radiographs are used in the surgical planning for dental implants, a safety margin of 2.5 mm (10.5%) should be added in the maxillary sinus area after compensating for image magnification.
Correlation between linear measurements of panoramic radiographs and cone beam computed tomography images of the maxillary sinus
Keywords: Cone beam computed tomography; Maxillary sinus; Radiography panoramic